Use of Egg Yolk Antibodies to Predict Optimal Age of Vaccination Against Infectious Bursal Disease (IBD) in Broilers - Boudaoud, A.; Mamache, B. (International Journal of Poultry Science, 2012)
Collecting sera from new-born chicks requires their sacrifice, which is an invasive and little economic method of sampling. We studied the possibility of replacing the antibody titres in serum of chicks by those in pre-incubated egg yolk for determining the optimal Age of Vaccination (OAV) against Infectious Bursal Disease (IBD) by the Deventer formula. The study focused on 10 hyper-immunized broiler-breeder flocks. Yolk of pre-incubated eggs and sera of newborn chicks, originated from the same parent flock, were essayed by Enzyme-Linked Immunosorbent Assay (ELISA) to detect IBDV specific Maternally Derived Antibodies (MDA). ELISA titres in both types of samples were similar (p<0.05) and well correlated (r = 0.74, p<0.05). The difference between the two vaccination age estimations, based on egg yolk and serum antibodies respectively, was minimal (less than one day). This difference was independent of parent breeder-flock age (r = 0.04, p>0.05 NS). These results encourage the use of egg yolk in predicting the OAV against IBD instead of sera from sacrificed chicks.